Event studies theory, research, and policy for planned events - Getz, Donald 1949- (London Routledge, 2016)
"Event Studies is the only book devoted to developing knowledge and theory about planned events. It focuses on event planning and management, outcomes, the experience of events and the meanings attached to them, the dynamic processes shaping events and why people attend them"--Provide by publisher.
Part One: Basic Concepts in Event Studies -- 1. Introduction and Overview of Event Studies -- 2. The World of Planned Events -- Part Two: Foundation Disciplines and Closely- Related Fields -- 3. Foundation Disciplines -- 4. More Foundation Disciplines -- 5. Closely-Related Fields -- Part Three: Framework for Understanding and Creating Knowledge -- 6. The Event Experience and Meanings -- 7. Event Design -- 8. Antecedents and Decision-Making -- 9. Planning, Management of Events -- 10. Outcomes and the Impacted -- 11. Events and Public Policy -- Part Four: Conclusion -- 12. Science, Knowledge and Theory for Event Studies.
Keywords: Special events -- Planning; Special events -- Research; Special events -- Management